Fiscal policy, sovereign debt and economic growth in SADC economies: A panel vector autoregression analysis - Bongumusa Prince Makhoba; Irrshad Kaseeram (Cogent Economics & Finance)
This study estimates a Panel Vector Autoregressive (PVAR) approach to analyse the impact of fiscal policy and public debt on economic growth in Southern African Developing Communities (SADC). The study further estimated the fixed effects (FE) and random effects (RE) to verify the robustness of empirical findings. The results provide rigorous empirical evidence of a positive response of GDP growth due to shocks in government expenditure, employment, and public debt while gross capital formation exerts a negative effect on economic growth. The study proposes that fiscal authorities ought to focus on the adoption of prudent fiscal policies as a credible stabilization tool at the disposal of policymakers to safeguard stable and yet productive public finances consistent with sustainable economic prosperity. These may include addressing infrastructural development, soaring fiscal deficit, creation of jobs, and creating a conducive environment for both labour and capital-intensive projects to flourish in the SADC economies.